Pemberdayaan Masyarakat melalui Pengembangan Potensi Lokal Dawet Jabung Ponorogo Menggunakan Metode Pengembangan Sumber Daya Manusia Pokdarwis - Sholekah, Nurul (Yayasan Arrahman Nahdlatul Wathan, 2024)
Community empowerment is an important issue that can improve the welfare of individuals and communities. This approach needs to be implemented in villages, especially those aimed at empowering communities through human resource development, especially in Jabung Village. Human resource development (HRD) in the context of community empowerment in Ponorogo by utilizing the local potential of Dawet Jabung is carried out through a structured and participatory approach. The Community Awareness Group (POKDARWIS) which is the main target of this program is given training in Organizational Management, Operational Management, Tourism Management, and Community-Based Tourism Management. The goal of this program is to increase community awareness and participation in developing local potential in order to improve the regional economy. Development methods include a series of managerial training, digital marketing workshops, and the Dawet Jabung Museum workshop. The expected output is the management of the culinary potential of Dawet Jabung as a cultural heritage of Ponorogo, as well as community commitment and consensus in the mission of establishing the